ANALISIS PENGELOLAAN KEUANGAN DAERAH BERBASIS DIGITAL DI KOTA PALANGKA RAYA - Amaliah, Elya; Siburian, Sriafni Y; FRiskila, Alia; Lumban Raja, Purada Riska Uli; Simbolon, Pebrita; Widyaningsih, Rice; Septriana, Marsya (Universitas Cenderawasih, 2025)
This study aims to analyze the effectiveness of digitally-based regional financial management in Palangka Raya City, evaluating the extent to which digital transformation affects fiscal governance, regional autonomy, and the quality of public services. Employing a qualitative case study approach, the method included analysis of secondary APBD data (2021-2024), in-depth interviews with local government officials (BPKAD, Bapenda, TP2DD), and documentation studies. The findings indicate that the implementation of the Regional Government Electronic Transactions (ETPD) policy has successfully served as a key instrument for enhancing efficiency and transparency in financial management. ETPD significantly strengthens the Internal Control System (ICS) and accelerates bookkeeping and reporting cycles. However, Palangka Raya City's fiscal performance is still shadowed by a heavy dependence on central transfer funds and the domination of employee expenditure, which hinders productive digital investment allocations. The main challenges identified are non-technical, including limited Human Resources (HR) capacity among officials to operate complex systems and uneven digital infrastructure in peripheral areas. Furthermore, community participation in budget oversight (horizontal accountability) requires improvement. This study recommends the optimization of Local Own-Source Revenue (PAD) through the expansion of ETPD into strategic local economic sectors, such as tourism and MSMEs, along with massive HR capacity building, as key measures to realize effective, accountable, and sustainable digital financial governance.